Development of the FAST-M Maternal Sepsis Bundle for Use in Low-resource Settings: A Modified Delphi Process. Issue 4 (December 2020) - Lissauer, D.; Chesire, J.; Dunlop, C.; Taki, F.; Wilson, A.; Smith, J.M.; Daniels, R.; Kissoon, N.; Malata, A.; Chirwa, T.; Lwesha, V.M.; Mhango, C.; et al.
Abstract : ( BJOG . 2020;127:416–423) Although maternal sepsis is the third most common cause of global maternal mortality, there are no internationally recognized sepsis care bundles directed toward pregnant women that can be implemented in a low-resource setting. While the Surviving Sepsis Campaign's (SSC) care bundle has been associated with reduced mortality for the general population, only 1.5% of health care facilities in Africa are able to implement the SSC guidelines in their entirety. The need to develop and implement effective strategies to reduce the global burden of maternal and neonatal sepsis in low-resource settings has become increasingly important, as demonstrated by a recent global directive by the World Health Organization (WHO) and Jhpiego. This study aimed to accomplish this directive by developing a care bundle for the initial management of maternal sepsis in low-resource settings.